Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Volume Balok Berdasarkan Newman's Error Analysis (Nea) Pada Siswa Kelas VIII SMP Negeri 2 Sawit Tahun Ajar 2016/2017 - Ambarwati, Ulfa Riana; , Drs. Slamet HW, M.Pd (2017)
This research aims to describe students' errors in solving the story volume problem and analyze the factors causing students to make mistakes in solving the problem. The type of this research is qualitative deskriptive. The subjects of this study are students of class VIII C SMP Negeri 2 Sawit academic year 2016/2017. Data collection methods used were interviews and documentation. The validity of data used is triangulation technique. Data analysis techniques by reducing data, presenting data, and drawing conclusions. The results showed that students made mistakes in solving the story volume of the beam. The types of problems that students do are (1) mistakes in understanding the meaning of the matter of 16.80%; (2) errors in the application of the concept of 21.60%; (3) errors in the calculation of 32.80%. Factors that cause students to make mistakes understand the meaning of the problem is that students still do not know what is known and asked in the matter. The cause of misconceptions made by students ie students do not know the formula of completion, mastery of low student volume material, and students do not know the step of completion in accordance with the procedure. Errors made by students in the calculation of students' problems in writing, students have not mastered the operation in mathematics and students are less thorough because of the haste. Keywords: analysis, error, story problem, beam volume. .